Comicbook characters' facial features and actions and movements as two sources of humour: the case of Fullmetal Alchemist. Issue 5 (3rd September 2021) - Chen, Li-Chi; Hajndrych, Eryk
ABSTRACT: This paper analyses images and texts from Fullmetal Alchemist, a 27-volume Japanese comicbook series, and aims to illustrate and discuss how comicbook characters' facial features and active movements are used to visualise humour. As the ways that readers perceive humour while reading comics are influenced by many factors, both graphic and textual components are examined. The results show that various drawing skills and strategies are used to construct characters' facial features and movements as two sources of humour. Our qualitative analysis further shows that halftone effects, suppletion, and micropanels can all be used to construct characters' facial features in a funny manner. Furthermore, reduplication, macropanels, neo-amorphic panels, and mimetic words are used to humorously present characters' actions and movements. This paper suggests that as comicbook humour is multimodally constructed, its perception requires a reader to parse both graphic and textual components.